EFFECTS OF SALINE SOILS ON RICE PRODUCTIVITY - Komilov Sh.; Kadyrov B.; Bozorboyev N.; Ruzimov B. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract. In the ongoing experiments 2021-2023. The task was set to study the effect of flooding of rice paddies on the dynamics of the content of water-soluble salts and the salt regime on the value of rice yield. Analysis and dynamics of the soil salt regime shows that in the rice development phase after tillering until the beginning of waxy rice ripeness, the most optimal from the point of view of ensuring a favorable soil salt regime is a flood layer with a depth of 17-22 cm.